2019
DOI: 10.1055/s-0039-1696585
|View full text |Cite
|
Sign up to set email alerts
|

From Platelet-Rich Plasma to Advanced Platelet-Rich Fibrin: Biological Achievements and Clinical Advances in Modern Surgery

Abstract: In the past 20 years, the platelet concentrates have evolved from first-generation products, i.e., platelet-rich plasma (PRP) and plasma rich in growth factors to the second-generation products such as leukocyte-platelet-rich fibrin (L-PRF) and advanced platelet-rich fibrin (A-PRF). These autologous products with a higher leukocyte inclusion and flexible fibrin mesh act as a scaffold to increase cellular migration in the angiogenic, osteogenic, and antimicrobial potential of these biomaterials in tissue regene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 45 publications
(49 reference statements)
1
68
0
4
Order By: Relevance
“…Physiologically, the growth factors in PRP have important roles in reducing the rate of aging by restoring the declining DNA synthesis that occurs with aging, resisting cell death and enhancing gene expression for tissue repair (25,26). A positive correlation between PRP and skin anti-aging has also been reported in both pre-clinical and clinical practice (25)(26)(27)(28). Consistent with previous studies (17,26), the present clinical study showed that PRP treatment improved skin conditions, including increased skin thickness, enhanced collagen content and reduced pigmentation.…”
Section: Discussionmentioning
confidence: 99%
“…Physiologically, the growth factors in PRP have important roles in reducing the rate of aging by restoring the declining DNA synthesis that occurs with aging, resisting cell death and enhancing gene expression for tissue repair (25,26). A positive correlation between PRP and skin anti-aging has also been reported in both pre-clinical and clinical practice (25)(26)(27)(28). Consistent with previous studies (17,26), the present clinical study showed that PRP treatment improved skin conditions, including increased skin thickness, enhanced collagen content and reduced pigmentation.…”
Section: Discussionmentioning
confidence: 99%
“…10,13 PRF membranes enable the gradual and continual release of growth factors, a process which contributes to the healing of soft tissues. 41 This process includes a variety of cell types regulated by molecules which are themselves produced as part of the recipient's immunological response. These molecules include metalloproteases (MMPs) and their tissue inhibitors (TIMPs), which are responsible for remodeling the tissue collagen matrix.…”
Section: Molecular Parameters: Discussionmentioning
confidence: 99%
“…Platelet-rich plasma (PRP) is an autologous concentrate of platelets in a minute amount of plasma [ 9 ]. It is considered a first-generation concentrate using calcium glutamate/thrombin to activate coagulation and an anticoagulant solution of citrate phosphate dextrose adenine (CPDA) [ 10 , 11 ]. After activation by thrombin or calcium chloride, the platelets in PRP release various essential growth factors documented to be produced by platelets [ 12 ].…”
Section: Introductionmentioning
confidence: 99%